Ottoman- European correspondence during the reign of Sultan Suleiman the Magnificent (1520-1566) diplomatically (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
The research deals with one of the tools of diplomacy (correspondence) that took place between Sultan Suleiman the Magnificent 1520-1566 and the rulers of Europe, and it came as a result of important political events that occurred in the first half of the 16th century. From those conflicts and European ambitions, a series of delegations and letters flowed.The Ottoman-European correspondence reflected the diplomatic form in which the Sultan and his men dealt with the rulers of Europe. On the one hand, it exposed the true intentions of European policy and its goals, and on the other hand, it was considered one of the most important means that showed the Ottoman Sultan’s response in all frankness to requests that affected his rights or questioned his abilities. For the Europeans, these diplomatic correspondence represented another way to acquire the throne and lands, away from initiating direct military actions